Benefits of Telemedicine for Maternal Health: Access, Education, and Monitoring (Oshada, 2025)
This study aims to analyze the benefits of telemedicine on maternal health through three main dimensions: service access, health education, and technology-based pregnancy monitoring systems. Using a qualitative approach with a literature review method, this study examined 25 scientific articles published between 2020 and 2025 that were relevant to maternal health and telemedicine issues. A thematic analysis was conducted to identify patterns of findings indicating that telemedicine contributes significantly to increasing equitable access to antenatal care, strengthening maternal health literacy, and optimizing real-time pregnancy monitoring. The study results indicate that the use of digital platforms not only expands the reach of services but also increases pregnant women's participation in self-care and accelerates early detection of complications. However, the effectiveness of telemedicine is still influenced by infrastructure, digital literacy, and ethical and data security aspects. This study confirms that the integration of these three dimensions creates an adaptive, inclusive, and prevention-oriented maternal service ecosystem. These findings are expected to serve as a conceptual foundation for the development of equitable and sustainable technology-based maternal health policies in Indonesia.